Brief Counseling for Alcohol Misuse Among Trauma Patients: two Interventions and Influence of Baseline Use - Rogers, Jennifer L. (Journal of addictions & offender counseling, 2018)
This study examined whether baseline trauma patient characteristics and randomized participation in 1 of 2 brief interventions predicted changes in alcohol use at 6 months postintervention. Higher total Alcohol Use Disorders Identification Test (AUDIT) scores predicted greater changes, and specific AUDIT items were significant predictors.